REDUCTION OF CORRUPTION RISKS AS A NECESSARY CONDITION FUNCTIONING OF ROAD INDUSTRY ENTERPRISES - KUPALOVA, Halyna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to formulate the main measures to reduce corruption risks as a necessary condition for the effective functioning of road industry enterprises. Progressive changes in the road industry of Ukraine in recent years have been analyzed. An important step in reducing corruption risks was the reform of pricing, in particular in the issue of determining the cost of road works and services. Information about tender offers, procurement related to the repair and maintenance of highways has become open and available on the Prozorro platform and the Unified State Portal of Open Data. Despite the measures taken, corruption risks in the road industry remain high. The reasons for corruption in the Ukravtodor system, according to the interviewed employees, are the dishonesty of officials, the presence of private interest, the imperfection of legislation, the low level of salaries and the influence of third parties. The main factors and conditions for the reduction of corruption manifestations are the integrity of employees, the transparency of management decision-making and control over compliance with anti-corruption requirements. Activities to reduce corruption risks in the road construction system require the use of a systemic approach, which includes a set of management, social-psychological, legal and informational measures. Management measures include actions related to financial control, procurement monitoring. Social and psychological measures are aimed at forming a negative attitude towards corruption. Legal measures are based on the application of legal norms in the regulation of industrial and labor relations. Information measures include the transparency of public procurement, openness of databases on prices, tenders, procurement volumes, and anti-corruption information work.
Keywords: corruption; corruption risks; enterprise; road industry; reform; monitoring; management; roads; highways; road quality; road infrastructure; road construction and repair; public procurement; tender; competition; integrity